Mechanochemical synthesis of N-salicylideneaniline: thermosalient effect of polymorphic crystals - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nangia, Ashwini (IUCRJ, 2017)
Polymorphs of the dichloro derivative of N-salicylideneaniline exhibit mechanical responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs. The molecules are connected via the amide N-H center dot center dot center dot O dimer synthon and C-Cl center dot center dot center dot O halogen bond in the three crystal structures. A fourth high-temperature Form IV was confirmed by variable-temperature single-crystal X-ray diffraction at 180 degrees C. The behaviour of jumping exhibited by the polymorphic crystals of Forms I and III is due to the layered sheet morphology and the transmission of thermal stress in a single direction, compared with the corrugated sheet structure of Form II such that heat dissipation is more isotropic causing blasting. The role of weak C-Cl center dot center dot center dot O interactions in the thermal response of molecular crystals is discussed.
Keywords: crystal design; crystal engineering; Halogen bonding; hydrogen bonding; intermolecular interactions; materials science; mechanochemistry; polymorphism

Liquid-assisted grinding mechanochemical approach for direct amidation of pyridone-carboxylic acid to synthesize an intermediate used in anti-viral API's bictegravir and cabotegravir - Karche, Ranjit S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ChemistrySelect, 2026)
Mechanochemistry is viewed as an appealing alternative for the synthesis of various compounds, since it is regarded as an eco-friendly and economical method that can be performed under solvent-free reaction conditions. In this work, neat grinding and liquid-assisted grinding (LAG) methods for direct amidation of pyridone-carboxylic acid and 2,4,6-trifluorobenzylamine/2,4-difluorobenzylamine were studied using EDC.HCl as a coupling reagent to synthesize important intermediates used in the synthesis of anti-HIV drug molecules bictegravir, cabotegravir, and dolutegravir. The products were easy to separate as they easily precipitated out from water, and the purity of the products obtained was similar to 97% for the intermediates, thus avoiding the need for their purification. This process eliminated the use of organic solvents for the reaction as well as for the work-up and product purification. The reaction was scaled up on a 15-g scale, giving good yields of the intermediates. The process was found to be practical, scalable, and reproducible on a gram scale.
Keywords: amidation; bictegravir; cabotegravir; mechanochemistry